Multi-Step Combined Control Technology for Karst and Fissure Water Inrush Disaster During Shield Tunneling in Spring Areas - Huang, Xing; Li, Linfeng; Zhang, Chaofan; Liu, Bin; Li, Kejin; Shi, Hongbing; Jing, Boyu (Frontiers in Earth Science, 2021)
Shield tunneling in highly fractured karst water-rich conditions easily result in water inrush disaster or even cause the karst caves' roof collapse. Severe water inrush disasters have occurred during the EPBs of the Jinan Metro Line R1 advanced through a karst and fissure groundwater-rich limestone ground in the spring area. To cope with the extreme water inrush risk, a multi-step combined control technology was put forward. Firstly, detailed geological exploration was carried out by ahead geophysical prospecting using high-density resistivity method and geological radar, etc., and geological drilling from the ground surface. As a result, the karst caves' distribution orientation, size, fissure development degree, and water inflow channel were detected. Secondly, multi-step grouting was performed to strengthen the surrounding rock, including pre-grouting treatment and filling rock blocks to the big karst caves from the ground surface, multiple grouting with a small amount of inert slurry each time inside the tunnel, and secondary circumferential hoop grouting at the shield tail. Thirdly, the tunneling process was optimized, including optimizing the tunneling parameters, making full use of the EPB’s air-pressurized tunneling technology to press bentonite into the fractures around the excavation cabin to seal the fissure water, and using the EPB's drainage system and improving the muck conditioning to reduce the water inrush disaster. Meanwhile, shield protection slurry technology is applied to cutters inspection and replacement in the pressurized chamber under dynamic water flow environment of the spring terrain. The practice shows that the water inrush on the tunnel face is obviously alleviated after the shield machine advances into the grouting area. The water inflow on the tunnel face decreases from about 4 m3/h to less than 0.3 m3/h after the above-mentioned control, and the water seepage between the segmental lines reduces to almost zero. The average advance rate increased from 3 m/d without stopping or even zero to about 6 m/d. In addition, the treatments prevented the shield machine from jamming and the head descending. This study provided a reliable control method for shield tunneling through the karst and fissure water-rich area and played an essential role in protecting the spring water.